Association analysis of -429T/C receptor for advanced glycation end products (RAGE) gene polymorphism with type 2 diabetic retinopathy and serum soluble RAGE levels in Pakistani patients - Shazia Qayyum; Muhammad Afzal; Abdul Khaliq Naveed (Journal of the Pakistan Medical Association, 2021)
Objective: To investigate the association of receptor for advanced glycation end products (RAGE) gene polymorphism 429T/C (rs1800625) with diabetic retinopathy (DR) and serum soluble RAGE (sRAGE) levels in Pakistani patients with Type 2 diabetes. Methods: A case-control study, conducted from January 2017 to December 2018, including 150 healthy controls (HC), 150 diabetics without retinopathy (DWR) and 150 DR patients. Ethical approval was taken from Ethics Review Committee of Islamic International Medical College - Riphah International University (RIU). Genotyping for 429T/C was done by Tetra-primer amplification refractory mutation system – polymerase chain reaction (T-ARMS-PCR). Serum sRAGE levels were measured by enzyme-linked immunosorbent assay (ELISA). Data was analysed to calculate descriptive and inferential statistics to compare genotype/allelic frequencies, biochemical markers and serum sRAGE among three study groups. Results: The frequency of TT, TC and CC genotypes of 429T/C polymorphism were: 91.3%, 6.7%, 2% in HC, 88.6%, 8.7%, 2.7% in DWR and 84.7%, 12.0%, 3.3 % in DR groups. No significant association of 429T/C genotypic and allelic frequencies with DWR and DR along with its subtypes, non- proliferative (NPDR) and proliferative (PDR) was observed. Upon further stratifying NPDR into mild, moderate and severe, an association of heterozygous TC with severe NPDR was observed compared to DWR in univariate and multinomial regression analysis. Serum sRAGE levels were significantly high in PDR patients compared to DWR and were positively correlated with fasting plasma glucose (FPG) in DR group. Continuous...